Biotite-Calx Based Traditional Indian Medicine Sahastraputi-Abhrak-Bhasma Prophylactically Mitigates Allergic Airway Inflammation in a Mouse Model of Asthma by Amending Cytokine Responses - Balkrishna A (Dove Medical Press, 2021)
Acharya Balkrishna,1– 3 Siva Kumar Solleti,1,* Hoshiyar Singh,1,* Rani Singh,1 Niti Sharma,1 Anurag Varshney1,2,4 1Drug Discovery and Development Division, Patanjali Research Institute, Haridwar, Uttarakhand, India; 2Department of Allied and Applied Sciences, University of Patanjali, Patanjali Yog Peeth, Haridwar, Uttarakhand, India; 3Patanjali UK Trust, Glasgow, UK; 4Special Centre for Systems Medicine, Jawaharlal Nehru University, New Delhi, India*These authors contributed equally to this workCorrespondence: Anurag VarshneyDrug Discovery and Development, Patanjali Research Institute, NH-58, Near Bahadrabad, Haridwar, 249405, UttraKhand, IndiaTel +91 1334-244107 x7458Fax +91 1334 244805Email anurag@prft.co.inPurpose: Asthma is a heterogeneous airway inflammatory disease with limited therapeutic options. Traditional medicine is extensively used for treating various ailments including asthma. Sahastraputi-Abhrak-Bhasma (SPAB) is a biotite-calx based Indian medicine.Methods: We have tested for the anti-inflammatory and anti-asthmatic properties of SPAB, using a mouse model of ovalbumin-induced allergic asthma in-vivo and cell-based assays in-vitro. Histological analysis, qPCR and ELISA were performed to assess the pathology. SEM, EDX and XRD-analysis were performed to characterize the SPAB particles.Results: SEM, EDX and XRD-analysis identified the presence of SPAB particle of 100 nm–∼ 1μm diameter and contains annite-1M, aluminium silicate, kyanite, aluminium oxide, magnesium silicate, and maghemite in the samples. Ova-challenge resulted in severe inflammatory responses, airway remodelling and increased oxidative burden in lungs. Importantly, prophylactic treatment with SPAB significantly attenuated allergen induced leukocyte infiltration specifically eosinophils, lymphocytes, macrophages and neutrophils in BALF. Ova-induced mucus hypersecretion, peri-bronchial collagen deposition, inflammatory cell infiltration and bronchial epithelial thickening were significantly abrogated upon SPAB treatment. qPCR and ELISA analysis identified that allergen induced increases in IL-5, IL-13, IL-33, IFN-γ and IL-1β cytokines mRNA in whole lungs and the levels of IL-6, IL-1β and TNF-α proteins in BALF were significantly attenuated upon oral SPAB treatment. SPAB restored allergen induced decreases in anti-oxidant markers in lungs. In-vitro, SPAB attenuated the secretion of IL-6, and TNF-α from human bronchial epithelial cells and modestly inhibited NF-kB/AP-1 pathway in HEK cells.Conclusion: Taken together, our results experimentally validated the prophylactic ameliorative potential of the Indian classical medicine Sahastraputi-Abhrak-Bhasma against asthma associated airway inflammation.Keywords: Sahastraputi-Abhrak-Bhasma, asthma, physicochemical analysis, lung inflammation, cytokine, mica-medicine